Pola Kemitraan Yayasan Trikaya dalam Pengembangan Usahatani Padi Organik di Subak Purnajaya, Desa Lebih, Kecamatan Gianyar, Kabupaten Gianyar - ANAK AGUNG RISKHA ANINDITA; I WAYAN BUDIASA; I G A A LIES ANGGRENI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Trikaya Foundation Partnership Pattern in the Development of Organic RiceFarming in Subak Purnajaya, Lebih Village, Gianyar Sub-District, GianyarRegencyRice as one of agriculture's mainstay commodities in Gianyar Regency whichhasbig opportunity, but Subak Purnajaya in the Lebih Village only able to produce anaverage of 2.5 up to 3 tons/ha with conventional farming systems and do not get marketguarantee. Seeing these conditions, the Trikaya Foundation created an organic rice pilotproject by embracing farmers to be its partners. This study aims to: (1) Analyze thecharacteristics of Subak Purnajaya before the partnership is implemented; (2) Analyzethe pattern and mechanism of partnership that is applied; (3) Analyze the obstaclesfaced in realizing the sustainability of partnerships between the foundation and subaks.The analytical method used was qualitative and quantitative descriptive analysis. Theresults of the study showed that (1) The characteristics of Subak Purnajaya before thepartnership was implemented, namely the limited knowledge possessed by farmers andthe subak was still applying conventional farming systems; (2) The partnershipimplemented in the Subak Purnajaya was a pattern of Agribusiness OperationPartnership; (3) The foundation constraints had not optimally accommodated farmersproduction and limited infrastructure facilities, while the constraints of farmers found itdifficult to find harvesters during great harvest time and are still dependent on thefoundation. Based on the results of the research, the foundation should be able to utilizethe role of social media to reach a wider market segments and improve the managementsystem in establishing partnerships, while farmers continue practicing organic farmingbecause it is more profitable than the conventional systems.